Recombination Map of the Common Shrew, Sorex araneus (Eulipotyphla, Mammalia) - Borodin, Pavel M. (Genetics Society of America, 2008)
The Eurasian common shrew (Sorex araneus L.) is characterized by spectacular chromosomal variation, both autosomal variation of the Robertsonian type and an XX/XY(1)Y(2) system of sex determination. It is an important mammalian model of chromosomal and genome evolution as it is one of the few species with a complete genome sequence. Here we generate a high-precision cytological recombination map for the species, the third such map produced in mammals, following those for humans and house mice. We prepared synaptonemal complex (SC) spreads of meiotic chromosomes from 638 spermatocytes of 22 males of nine different Robertsonian karyotypes, identifying each autosome arm by differential DAPI staining. Altogether we mapped 13,983 recombination sites along 7095 individual autosomes, using immunolocalization of MLH1, a mismatch repair protein marking recombination sites. We estimated the total recombination length of the shrew genome as 1145 cM. The majority of bivalents showed a high recombination frequency near the telomeres and a low frequency near the centromeres. The distances between MLH1 foci were consistent with crossover interference both within chromosome arms and across the centromere in metacentric bivalents. The pattern of recombination along a chromosome arm was a function of its length, interference, and centromere and telomere effects. The specific DNA sequence must also be important because chromosome arms of the same length differed substantially in their recombination pattern. These features of recombination show great similarity with humans and mice and suggest generality among mammals. However, contrary to a widespread perception, the metacentric bivalent tu usually lacked an MLH1 focus on one of its chromosome arms, arguing against a minimum requirement of one chiasma per chromosome arm for correct segregation. With regard to autosomal chromosomal variation, the chromosomes showing Robertsonian polymorphism display MLH1 foci that become increasingly distal when comparing acrocentric homozygotes, heterozygotes, and metacentric homozygotes. Within the sex trivalent XY(1)Y(2), the autosomal part of the complex behaves similarly to other autosomes.